1991
DOI: 10.1029/91wr01567
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Simulation of the Subsidence of Ravenna

Abstract: Land subsidence at Ravenna is the result of aquitard and reservoir compaction caused, respectively, by extensive groundwater withdrawals from the unconsolidated Quaternary basin and gas production from a number of pre‐Quaternary pools scattered over the area. Water pumpage paralleled the postwar industrial development of Ravenna until the middle seventies when consumption was drastically curtailed owing to the economic crisis and the activation of a new aqueduct. Gas production started in 1952. The exploitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 18 publications
1
90
0
Order By: Relevance
“…Reservoir compaction is nowadays generally analyzed using partially or fully coupled numerical modeling approaches; see the paper by Lewis et al (2003) in this Special Issue. In a partially coupled approach, the pressure pattern obtained from reservoir simulators is used in a stress-strain analysis to compute the compaction of the reservoir and the subsidence of the land surface Freeze 1973 andGambolati et al 1991). However, fully coupled models based on Biot's theory of consolidation have also been used (e.g., Lewis and Schrefler 1998;Gutierrez et al 1995).…”
Section: Oil and Gas Extractionmentioning
confidence: 99%
“…Reservoir compaction is nowadays generally analyzed using partially or fully coupled numerical modeling approaches; see the paper by Lewis et al (2003) in this Special Issue. In a partially coupled approach, the pressure pattern obtained from reservoir simulators is used in a stress-strain analysis to compute the compaction of the reservoir and the subsidence of the land surface Freeze 1973 andGambolati et al 1991). However, fully coupled models based on Biot's theory of consolidation have also been used (e.g., Lewis and Schrefler 1998;Gutierrez et al 1995).…”
Section: Oil and Gas Extractionmentioning
confidence: 99%
“…Here the monitoring of ground elevation by traditional as well as more advanced techniques (see e.g. Bitelli et al, 2000) showed that the land-subsidence rate experienced a sudden acceleration in the aftermath of World War II due to an intense water and gas extraction from underground (Gambolati et al, 1991;Carminati et al, 2002). The latter produced more than 1.5 m cumulative lowering near the historical city centre of Ravenna (see Fig.…”
Section: Introductionmentioning
confidence: 93%
“…Other studies identified the exploitation of several on-shore and off-shore deep gas reservoirs in the Ravenna area as an additional factor that contributed to the growing of land-subsidence rate up to some centimeters per year (see e.g. Gambolati et al, 1991). In 2005, Teatini et al (2005) pro-vided a detailed georeferenced map of land-subsidence in the eastern Po River plain over the period 1897-2002, based on the main levelling surveys databases available in the Ravenna area for the last century (IGM, Ravenna Reclamation Authority, Geological Service of the Ravenna Municipality, ARPA and ENI-E&P).…”
Section: Study Areamentioning
confidence: 99%
“…We considered the area close to the city of Ravenna (Italy), as it is the most prominent example of human-accelerated land subsidence in Italy. Due to intense extraction of underground water and natural gas, the study area underwent extremely significant ground lowering during the last century, with a cumulative drop greater than 1.5 m in a century in the historical centre of the city, horizontal gradients above 0.3 m km −1 , and lowering rates larger than 110 mm year −1 , when the natural rate is estimated as a few mm year −1 (see Gambolati et al 1991, Carminati and Martinelli 2002, Teatini et al 2005). …”
Section: Discussionmentioning
confidence: 99%
“…The local rate of land subsidence is naturally in the order of a few mm per year, but it increased enormously after World War II, as shown, for example, in the ground elevation analysis by Bitelli et al (2000), most likely due to an increase in the extraction of deep non-renewable groundwater associated with the economic growth and industrial expansion of the area. Gambolati et al (1991) showed how this and the subsequent exploitation of several on-shore and off-shore deep gas reservoirs in the Ravenna area increased the rate of land subsidence up to several centimetres per year. The close relationship between groundwater pumping and land subsidence has been confirmed by numerous studies.…”
Section: Study Areamentioning
confidence: 99%